Kebijakan Mandatori Sertifikasi Halal bagi Produk Usaha Mikro, Kecil, dan Menengah di Kabupaten Kudus - umi latifah (JIOSE: Journal of Indonesian Sharia Economics, 2022)
Enactment of Law No.33 Th. 2014 or the Law on Halal Product Guarantee (Act JPH) and PP No.31 Th. 2019 as a guide for implementing the JPH Law has the consequence of having halal certification obligations on all products in circulation. Revealed again in PMK RI No. 57/PMK.05/2021. This process requires stakeholder readiness and education for industry players throughout Indonesia, including Kudus Regency. The existence of this policy raises the problem of how to implement it in the field. This study aims to determine its implementation, responses from MSMEs, challenges and opportunities for MSMEs.This research is field research with data collection methods through interviews, observations, and document studies. The data processing through the making of transcripts, codes, and categorization. Then analyzed using qualitative analysis. The result of the research shows that the implementation of Act JPH in the Kudus Regency has not been optimal. It is shown from the implementation activities, communication between stakeholders, and implementing tendencies in implementing policies. This research also finds there are various challenges to be faced and opportunities that can be utilized for MSMEs with the existence of a mandatory halal certification policy.